Biomarker-based prediction of progression in MCI: Comparison of AD-signature and hippocampal volume with spinal fluid amyloid-β and tau - Dickerson, Bradford C.; Wolk, David (Frontiers in Aging Neuroscience, 2013)
OBJECTIVE: New diagnostic criteria for MCI due to AD have been developed using biomarkers aiming to establish whether the clinical syndrome is likely due to underlying AD. We investigated the utility of MRI and CSF biomarkers in predicting progression from amnesic MCI to dementia, testing the hypotheses that 1) markers of amyloid and neurodegeneration provide distinct and complementary prognostic information over different time intervals, and that 2) evidence of neurodegeneration in amyloid-negative MCI individuals would be useful prognostically. METHODS: Data were obtained from the ADNI-1 database on all individuals with a baseline diagnosis of MCI, baseline MRI and CSF data, and at least one follow-up visit. MRI data were processed using a published set of a priori regions of interest to derive a measure known as the “AD-signature”, as well as hippocampal volume. The CSF biomarkers amyloid-b, total tau, and phospho tau were also examined. We performed logistic regression analyses to identify the best baseline biomarker predictors of progression to dementia over 1 or 3 years, and Cox regression models to test the utility of these markers for predicting time-to-dementia. Results: For prediction of dementia in MCI, the AD signature cortical thickness biomarker performed better than hippocampal volume. Although CSF tau measures were better than CSF amyloid-β at predicting dementia within 1 year, the AD signature was better than all CSF measures at prediction over this relatively short-term interval. CSF amyloid-β was superior to tau and AD signature at predicting dementia over 3 years. When CSF amyloid-β was dichotomized using previously published cutoff values and treated as a categorical variable, a multivariate stepwise Cox regression model indicated that both the AD-signature MRI marker and the categorical CSF amyloid-β marker were useful in predicting time-to-event diagnosis of AD dementia. CONCLUSIONS: In amnesic MCI, short-term (1 year) prognosis of progressio